Nipah Virus Outbreak in India - Hussain, Rabia; Azmi Hassali, Mohamed; Patel, Isha (Indian Journal of Pharmacy Practice)
The notorious Nipah virus is again in action in India and in May 2018 it has took 19 lives in Indian states named Kerala and Karnataka.1 A total of 19 cases have been reported to be under treatment for the virus.1 The situation has raised a concern among general population and healthcare officials in India2 and many countries, such as Bahrain and United Arab Emirates has issued a travel advisory to its nationals to avoid visit to infected areas.3 The virus in India is linked to fruit bats from family Pteropodidae, which are commonly known as flying foxes in India and are a major source of infection in both animals and humans.4 A Nipah viral outbreak was previously seen in Bangladesh in 2013- 2014,4 where the villagers drank palm tree sap and got sick.5 Upon investigation, it was found out that the palm tree sap (a national delicacy of Bangladesh) was contaminated by the urine and saliva of bats that contaminated the sap during nighttime. The villagers left pots uncovered at night for sap collection.5